2003
DOI: 10.1128/aem.69.11.6527-6532.2003
|View full text |Cite
|
Sign up to set email alerts
|

Gene Dosage Effect of l -Proline Biosynthetic Enzymes on l -Proline Accumulation and Freeze Tolerance in Saccharomyces cerevisiae

Abstract: We have previously reported that L-proline has cryoprotective activity in Saccharomyces cerevisiae. A freezetolerant mutant with L-proline accumulation was recently shown to carry an allele of the PRO1 gene encoding ␥-glutamyl kinase, which resulted in a single amino acid substitution (Asp154Asn). Interestingly, this mutation enhanced the activities of ␥-glutamyl kinase and ␥-glutamyl phosphate reductase, both of which catalyze the first two steps of L-proline synthesis and which together may form a complex in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 35 publications
6
40
0
1
Order By: Relevance
“…Proline is believed to function as a compatible solute and as a free-radical scavenger to protect macromolecular structures form damage during osmotic and oxidative stresses (46,47). We also found that intracellular proline in yeast has an important role in reducing the oxidative stress induced during freezing and thawing or during exposure to H 2 O 2 (26,(48)(49)(50). It is therefore suggested that the toxic accumulation of P5C, not proline, triggers oxidative damage in yeast cells by reacting with various cellular compounds.…”
Section: Toxic Accumulation Of P5c Causes Oxidative Damage In Yeast Cmentioning
confidence: 72%
“…Proline is believed to function as a compatible solute and as a free-radical scavenger to protect macromolecular structures form damage during osmotic and oxidative stresses (46,47). We also found that intracellular proline in yeast has an important role in reducing the oxidative stress induced during freezing and thawing or during exposure to H 2 O 2 (26,(48)(49)(50). It is therefore suggested that the toxic accumulation of P5C, not proline, triggers oxidative damage in yeast cells by reacting with various cellular compounds.…”
Section: Toxic Accumulation Of P5c Causes Oxidative Damage In Yeast Cmentioning
confidence: 72%
“…For example, a mutant form of PUT1 encoding an enzyme from the proline biosynthetic pathway was isolated from yeast mutants with increased proline levels (228). In contrast to the wild-type enzyme, the mutated version of Put1p was less sensitive to feedback regulation by proline, and its overexpression led to intracellular accumulation of proline (310,347).…”
Section: In Vivo Protein Activitymentioning
confidence: 99%
“…Although a twohybrid analysis showed a physical interaction between tQM and Put1p, it remains to be clarified how tQM increases the intracellular proline concentration and protects the PUT1-overexpressing strain from oxidative stress (54). It is worth noting that high intracellular proline also positively affects freeze tolerance (347), desiccation (340), and ethanol tolerance (339,341) in yeast (see below and "Improving tolerance to ethanol" below). If present in the medium, proline may also serve as an osmoprotectant in yeast (349).…”
Section: Food and Beverage Industrymentioning
confidence: 99%
“…Proline also has an established role in defending against various abiotic and biotic stresses with its properties as a compatible solute benefiting a broad-range of organisms [10][11][12][13][14][15][16][17][18][19][20]. Proline has been shown to diminish aggregation of the polyQ region of the huntington protein suggesting a preventive role of proline in neurodegenerative diseases [19].…”
Section: Introductionmentioning
confidence: 99%